Pola Komunikasi Tutor Dalam Penggunaan Metode Belajar Unik Satu Murid Satu Tutor di LKP SAS English Laboratory - Hasibullah, Ridho; Hendra, Yan (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
The purpose of the study was to analyze the tutor communication pattern through the use of the "one student one tutor" method at the SAS English Laboratory LKP and to identify its benefits for students' understanding and learning motivation. This type of research uses a qualitative approach. Data collection through observation, interviews and literature review. The research data was processed using qualitative analysis that refers to interpersonal communication theory. The results of the study showed that tutors used a combination of verbal and nonverbal communication to convey material, build closer interactions with students, and increase learning effectiveness. Factors such as communication intensity, use of learning media, and strategies to overcome communication barriers are very useful in building an active and productive learning atmosphere. This finding confirms that effective tutor communication patterns can increase students' motivation and understanding of English learning materials. Therefore, the use of more innovative communication techniques and the use of learning media are needed to support the success of the "one student one tutor" method.